Insights From the Particle Impact Model Into the High‐Frequency Seismic Signature of Debris Flows. Issue 1 (9th January 2021) - Zhang, Zhen; Walter, Fabian; McArdell, Brian W.; Wenner, Michaela; Chmiel, Małgorzata; de Haas, Tjalling; He, Siming
Abstract: Debris flows induce seismic ground unrest detectable over large distances. However, recent theoretical description of debris‐flow seismograms has yet to be implemented in alarm systems. Here, we test the implications of a particle impact model for debris‐flow detection and warning using seismic data. We analyze 14 debris flows at Illgraben, Switzerland, using instantaneous weight measurements, a seismic network and video footage. A novel approach to simulate seismic wave propagation estimates both vertical and horizontal particle impact forces on the ground. Scaling between impact forces, weight, and particle sizes suggests that seismic data identify destructive debris flows with large boulders. Impact force spectra change with bed topography and increase during flow propagation of large events, but decrease for smaller events. This can be explained with the known conveyor mechanism concentrating boulders at the flow front. Our results highlight opportunities to use seismic data for debris‐flow research and warning. Plain Language Summary: Debris flows are muddy mixtures of water, sand, and boulders, which move down steep mountain creeks in an uncontrolled way. They are a major threat to human life, properties, and infrastructure. Ground vibrations generated by debris flows contain information on the characteristics of debris flows that are difficult to measure with conventional methods. However, these ground vibrations are complex and challenging to understand so that scientists struggle to use them for quantitative studies. Here we treat the interaction between debris flows and the ground as many particles randomly bouncing off the channel bed. We can thus simulate the ground vibrations generated by such particle/ground impacts for 14 debris flows at Illgraben, Switzerland. Our results show that particle/ground impacts correlate with the weight of the debris flow. For small events, ground vibrations decrease along the flow path. In contrast, for large‐volume debris flows, vibrations gradually increase. This is related to sediment erosion and deposition showing how ground vibrations characterize debris flows. Key Points: Impact force spectra of debris flows are inverted using high‐frequency seismic signals Inverted force spectra are coherent with in situ measurements at a force plate and contain information about particle sizes Evolution of inverted force spectra of debris flows indicates variations in bed topography